1997
DOI: 10.1520/jfs14223j
|View full text |Cite
|
Sign up to set email alerts
|

Recidivism and Concomitant Criminality in Pathological Firesetters

Abstract: The purpose of this study was to explore dangerousness and fire setting recidivism of mentally disordered firesetters in comparison with mentally healthy arsonists. In Germany, all trials are registered centrally by the Federal Central Register. The records of this Register for the three year period from 1983 until 1985 were used in this follow-up study of arsonists to identify three samples of subjects: (1) All persons convicted of arson who have been found not guilty by reasons of insanity (n = 186), (2) all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The most prevalent symptoms included delusions (35.2%), psychosis (33.8%), paranoia (29.6%), depression (25.4%), and suicidality (11.3%). The presence of a mental illness has also been consistently reported in the literature as a risk factor for repeat firesetting (Barnett, Richter, Sigmund, & Spitzer, 1997;Dickens, Sugarman et al, 2009;Lindberg et al, 2005;O'Sullivan & Kelleher, 1987). Clearly, more definitive research is required in order to explore the exact links between mental health and firesetting.…”
Section: Association Between Firesetting and Mental Illnessmentioning
confidence: 96%
See 3 more Smart Citations
“…The most prevalent symptoms included delusions (35.2%), psychosis (33.8%), paranoia (29.6%), depression (25.4%), and suicidality (11.3%). The presence of a mental illness has also been consistently reported in the literature as a risk factor for repeat firesetting (Barnett, Richter, Sigmund, & Spitzer, 1997;Dickens, Sugarman et al, 2009;Lindberg et al, 2005;O'Sullivan & Kelleher, 1987). Clearly, more definitive research is required in order to explore the exact links between mental health and firesetting.…”
Section: Association Between Firesetting and Mental Illnessmentioning
confidence: 96%
“…However, compared to non-mentally disordered firesetters, mentally disordered firesetters appear to be older (Barker, 1994;Barnett et al, 1997;Smith & Short, 1995). It has been suggested that this difference in age is due to the fact that psychiatric illnesses (e.g., schizophrenia and personality disorders) have a propensity to onset in early adulthood (Smith & Short, 1995).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that differences in rates may be due to population differences with mentally disordered samples perhaps exhibiting somewhat lower rates as a result of positive response to psychotherapeutic/pharmacological interventions. However, it appears that mental disorder in and of itself is not necessarily predictive of reoffending generally (see Barnett, Richter, et al, 1997). Certainly, at least one review has queried support for the notion of arsonists as dangerous recidivists (Brett, 2004) and, in general, it appears that arsonists will typically commit more than one arson offence, but that previous arson offending is not necessarily prognostic of future arson activity.…”
mentioning
confidence: 99%